Food Safety Policy, Implications for MSME Green Economy Based Product Processing - Rudiatin, Endang; Putri, Dessy Iriani; Rahma, Irhamni (Universitas Muhammadiyah Jakarta, 2024)
Processed food production plants are implementing the Food Safety Risk Management Program in accordance with BPOM Regulation Number 10 of 2023. Indonesian food safety surveillance is based on a preventive, risk-based paradigm where producers bear the main responsibility for food safety. The research's objective is to offer solutions to micro, small, and medium-sized firms (MSMEs) so that these businesses may also guarantee the quality and safety of their goods while working within the constraints of available facilities and resources for manufacturing and distribution.The study's conclusions imply that MSMEs should receive risk management training for food safety, which should include instruction on how to integrate halal practices into their production processes. Through zero waste, environmental friendliness, and energy efficiency, this research presents a strategy for implementing technological innovation based on a green economy. The basic concept of halal products requires business operators to manage the food processing in a series that includes zero waste activities, environmentally friendly practices, and energy efficiency within a single production process. This process is ensured to be an implementation of food safety risk management programs. The research's conclusions suggest that MSME actors could find it easier to understand and implement this strategy. Now that the risks to food security have been eliminated, the halal certification procedure can proceed.